A man - Hirano, Keiichirō 1975- (Amazon Crossing, 2020)
"Akira Kido is a divorce attorney whose own marriage is in danger of being destroyed by emotional disconnect. With a midlife crisis looming, Kido's life is upended by the reemergence of a former client, Rié Takemoto. She wants Kido to investigate a dead man--her recently deceased husband, Daisuké. Upon his death she discovered that he'd been living a lie. His name, his past, his entire identity belonged to someone else, a total stranger. The investigation draws Kido into two intriguing mysteries: finding out who Rié's husband really was and discovering more about the man he pretended to be. Soon, with each new revelation, Kido will come to share the obsession with--and the lure of--erasing one life to create a new one"--Jacket
Keywords: Identity (Philosophical concept) / Fiction; Identity (Philosophical concept); Legal stories; Detective and mystery fiction; Fiction; Legal fiction (Literature); Fiktionale Darstellung